التدفق النفسي: دراسة مقارنة بين الموهوبين والعاديين من طلبة مرحلتي الأساس والثانوي بولاية الخرطوم - بخيت، صلاح الدين فرح عطا الله; علي، سهام علي طه (مكتب التربية العربي لدول الخليج, 2022)
استهدفت الدراسة الحالية إجراء دراسة مقارنة بين الموهوبين والعاديين في التدفق النفسي، وكذلك دراسة تأثر التدفق النفسي ببعض المتغيرات الديموغرافية والتصنيفية لدى المشاركين في الدراسة. أعد الباحثان مقياس التدفق النفسي المكون من (36) بندا، وبعد التحقق من صدقه وثباته، تم تطبيقه على 1258 طالبا وطالبة من الموهوبين والعاديين، متوسط، أعمارهم (12.71 سنة، بانحراف معياري 2.5). وباستخدام تحليل التباين الثلاثي تم تحليل بيانات الدراسة، وكشفت نتائج الدراسة عن الآتي: - وجود فروق دالة إحصائيا في التدفق النفسي تعزى لمتغير التصنيف (الموهوبين* والعاديين) لصالح الموهوبين، وكذلك وجود فروق دالة إحصائيا تعزى لمتغير الجنس (ذكور وإناث) لصالح الإناث. - عدم وجود فروق دالة إحصائيا في التدفق النفسي تعزى لمتغير المرحلة التعليمية (أساس* وثانوي). - وجود فروق دالة إحصائيا في التدفق النفسي تعزى للتفاعل بين متغيري (التصنيف والمرحلة التعليمية، ووجود فروق تعزى للتفاعل بين المتغيرات الثلاثة (التصنيف * الجنس * المرحلة التعليمية). - وعدم وجود فروق دالة إحصائيا في التدفق النفسي تعزى للتفاعل بين متغيري (التصنيف * والجنس)، وكذا بين متغيري (الجنس * المرحلة التعليمية). The current study aimed to conduct a comparative study between the gifted and the and none gifted students in psychological flow, as well as to study the influence of psychological flow on some demographic and classification variables in the study participants. The researchers prepared a psychological flow scale consisting of (36) items, and after verifying its validity and reliability, it was administered to 1258 gifted and none gifted male and female students, their average age (12.71 years, standard deviation of 2.5). Using Three-way analysis of variance, the data were analyzed, and the results of the study revealed the following: - There are statistically significant differences in the psychological flow due to the classification variable (gifted and none gifted) in favor of the gifted, as well as the presence of statistically significant differences due to the gender variable (males and females) in favor of females. -There are no statistically significant differences in psychological flow due to the educational stage variable (basic and secondary). -There are statistically significant differences in the psychological flow due to the interaction between the variables of classification and the educational stage, and the presence of differences due to the interaction between the three variables (classification * gender * educational stage). - There are no statistically significant differences in the psychological flow due to the interaction between the variables (classification * and gender), nor between the variables (gender * educational stage).
Keywords: علم النفس الإيجابي -- التدفق النفسي -- الطلبة المتفوقون -- المدارس الحكومية -- السودان